Antimicrobial activities of highly bioavailable organic salts and ionic liquids from fluoroquinolones - Santos, Miguel M. (2021)
UIDB/50006/2020 PTDC/QUI-QOR/32406/2017 PEst-C/LA0006/2013 RECI/BBBBQB/0230/2012